Correlation of Mufrodat Mastery and Maharah Qira'ah Arabic Text - Fika Nadiya Ummi Salwa; Mu'at Mu'at Mu'at (Institut Dirosat Islamiyah Al-Amien Prenduan, 2023)
Vocabulary which is the most important tool in Arabic language education, students can understand Arabic because they have enough vocabulary. Therefore, students' vocabulary mastery has a great impact on Arabic language education. The research questions of this study are: (1) What is the result of